Types of affiliation in the hotel sector: an insight into the Portuguese experience - Almeida, Sofia (2022)
This study analyses the types of affiliation in the hotel sector and identifies the factors that affect the choice of affiliation. Accordingly, this study’s objectives are: i) to analyse managers’ perceptions regarding the most appropriate type of affiliation; and ii) to uncover the factors that influence the type of affiliation they choose. Data was collected through a questionnaire. Findings show that management contracts and marketing consortia are adequate affiliation types for four- and five-star hotels. The terms of the contract, followed by the chain’s affiliation strategy, were the most important factors that most influence this choice. Limitations, theoretical and managerial contributions are presented in the end.